Answering Questions About Race: How Racial and Ethnic Identities Influence Survey Response. Issue 2 (March 2019) - Abrajano, Marisa; Alvarez, R. Michael
Given the fundamental role that race and ethnicity play in U.S. society, sensitive survey items on this subject can often lead individuals to underreport their true attitudes. Previous studies have shown that the absence of an interviewer reduces the pressure to provide socially desirable responses. The 2012 and 2016 American National Election Studies (ANES), where both interviewer and self-administered surveys were used, allows us to test whether mode effects emerge in the way respondents answer survey items related to racial attitudes. We also expect mode effects to vary based on the extent to which individuals are politically socialized in the United States. We find that respondents tend to underreport their racial animosity in interview-administered versus online surveys. Moreover, underreporting is nonexistent in the responses provided by foreign-born Latinos, but emerges for U.S.-born Latinos, Blacks, and Whites. These findings pose a number of implications for our understanding of racial attitudes and survey mode.